Indole 3-Butyric Acid Metabolism and Transport in Arabidopsis thaliana - Damodaran, Suresh; Strader, Lucia C. (Frontiers in Plant Science, 2019)
Auxin is a crucial phytohormone involved in multiple plant developmental processes. Spatiotemporal regulation of auxin levels is necessary to achieve development of organs in the proper place and at the proper time. These levels can be regulated by conversion of auxin (indole 3- acetic acid; IAA) from its conjugated forms and its precursors. Indole 3-butyric acid (IBA) is an auxin precursor that is converted to IAA in a peroxisomal β-oxidation process. In Arabidopsis altered IBA-to-IAA conversion leads to multiple plant defects, indicating that IBA contributes to auxin homeostasis in critical ways. Like IAA, IBA and its conjugates can be transported in plants, yet many IBA carriers still need to be identified. In this review, we discuss IBA transporters identified in Arabidopsis thus far, including the PDR (PLEIOTROPIC DRUG RESISTANCE) members of the ABCG (G Subfamily of ATP BINDING CASSETTE transporter) family, the TOB1 (TRANSPORTER OF IBA1) member of the MFS (major facilitator superfamily) family and hypothesize other potential IBA carriers involved in plant development.